EVALUASI PENJAMINAN MUTU PENDIDIKAN DI SMP NEGERI 1 ABUNG BARAT LAMPUNG UTARA - Prasetyo Hidayat; Sulton Djasmi; Sowiyah Sowiyah (9 772338317006)
This thesis intended to evaluate the implementation of quality assurance programs of education in SMP Negeri 1 Abung Barat school year 2013/2014 by using the Context, Input, Process, Product (CIPP) model, through the evaluation approach with a qualitative description method. The results showed that: in the aspect of context, education quality assurance program provided quality education to the community, and enhance the prestige of the school. In the aspect of the input consists of two components, namely teacher standards, and management standards, the average 86.04% compliance with both criteria. In the aspect of the process consists of three components: content standards, processes standardized and evaluation standard with 75.66% moderate criteria. In the aspect of products standard which were measured was a graduate standard, this standard fulfillment is 100%. Based on the grouping of five national standards, SMP Negeri 1 Abung Barat is the school towards SNP group 3, with a value of five national education standards was 79.81 (? 6.5).Tesis ini bertujuan mengevaluasi pelaksanaan program jaminan kualitas pendidikan di SMP Negeri 1 Abung Barat tahun ajaran 2013/2014 dengan menggunakan model Context, Input, Process, Product (CIPP), melalui pendekatan evaluasi dengan metode deskripsi kualitatif . Hasil penelitian menunjukkan: Dalam aspek konteks, program jaminan kualitas pendidikan memberikan pendidikan yang berkualitas kepada masyarakat, dan meningkatkan prestise sekolah. Dalam aspek input terdiri dari dua komponen, yaitu standar guru, dan standar pengelolaan, rata-rata 86,04% sesuai dengan kriteria. Dalam aspek proses terdiri dari tiga komponen: standar isi, standar proses dan standar penilaian dengan 75,66% kriteria sedang. Dalam aspek standar produk yang diukur adalah standar lulusan, pemenuhan standar ini adalah 100%. Berdasarkan pengelompokan lima standar nasional, SMP Negeri 1 Abung Barat Menuju kelompok SNP 3, dengan nilai lima standar pendidikan nasional adalah 79,81 (? 6,5).Kata kunci: CIPP, evaluasi progam, penjaminan mutu pendidikan